2020
DOI: 10.3390/nano10050907
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Magnetic Core-Shell CoFe2O4@MnFe2O4 Nanoparticles for In Vivo Theranostics

Abstract: In this work, we report the synthesis and characterization of three magnetic nanosystems, CoFe2O4, CoFe2O4@ZnFe2O4, and CoFe2O4@MnFe2O4, which were developed as potential theranostic agents for magnetic hyperthermia and magnetic resonance imaging (MRI). These nanosystems have been thoroughly characterized by X-ray Diffraction (XRD), Transmission Electron Miscroscopy (TEM), Dark Field-TEM (DF-TEM), Vibrating Sample Magnetometry (VSM), and inductive heating, in order to elucidate their structure, morphology, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…With regards to the improvement in SLP due to an interphase exchange mechanisms [26], an example shows synergistic effects (SLP~500 W/g) in soft MnFe 2 O 4 and hard CoFe 2 O 4 bimagnetic clusters when compared with the homomagnetic 9 nm counterparts (~100 and~200 W/g for Mn-and Co-ferrite, respectively) [27]. Such SLP values are similar to many others in the literature [28][29][30][31][32][33]. Overall, despite the superior magnetic hyperthermia response in many core-shell systems, recent experimental and theoretical studies failed to reproduce heating efficiencies above a few hundreds of watts per gram [34], in line with our observations (Table 2).…”
Section: Comparison With Other Core-shell Systemssupporting
confidence: 82%
“…With regards to the improvement in SLP due to an interphase exchange mechanisms [26], an example shows synergistic effects (SLP~500 W/g) in soft MnFe 2 O 4 and hard CoFe 2 O 4 bimagnetic clusters when compared with the homomagnetic 9 nm counterparts (~100 and~200 W/g for Mn-and Co-ferrite, respectively) [27]. Such SLP values are similar to many others in the literature [28][29][30][31][32][33]. Overall, despite the superior magnetic hyperthermia response in many core-shell systems, recent experimental and theoretical studies failed to reproduce heating efficiencies above a few hundreds of watts per gram [34], in line with our observations (Table 2).…”
Section: Comparison With Other Core-shell Systemssupporting
confidence: 82%
“… 206 Among them, ZnFe 2 O 4 , MnFe 2 O 4 , CoFe 2 O 4 nanoparticles were widely investigated. 207 For example, Meidanchi et al confirmed that ZnFe 2 O 4 nanoparticles interacted with γ-rays to produce photoelectric effect resulting in a higher release level of electron in radioresistant cells. 208 Studies also indicated that ZnFe 2 O 4 nanoparticles could be used as radiosensitizers.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Even more impressive results were obtained with Zn 0.4 Fe 2.6 O4@CoFe 2 O 4 core-shell MNPs prepared with a cubic shape in which the SAR was above 10 kW/g [ 105 ]. Although these are outstanding SAR values compared to other MNPs [ 106 ], the synthesis of homogeneous core-shell structures with a controlled shell thickness remains a challenge.…”
Section: Mnps For Mhtmentioning
confidence: 99%